2022
DOI: 10.3389/fneur.2022.827544
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Profiles Revealed Alterations in Patients With Meibomian Gland Dysfunction After Exposure to Intense Pulsed Light

Abstract: So far, intense pulsed light (IPL) has been widely used in the treatment of meibomian gland dysfunction (MGD), but there was still a lack of research on its specific mechanism. Determining whether there was a correlation between liposome changes and remission of clinical signs in patients with MGD treated with IPL was of great significance in the clinical evaluation of efficacy in patients with MGD. Our study enrolled the 10 healthy subjects and 26 adult patients, who were diagnosed with MGD and had not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several authors have promoted this as a contributary mechanism of IPL (Dell et al, 2017; Gupta et al, 2016), though others voice scepticism due to the short duration and limited effect on temperature (Albietz & Schmid, 2018; Craig et al, 2015). However, recent publications describe alterations of the lipidomic profile of DED patients following IPL treatment, thus theoretically lowering the phase‐transition temperature back towards the physiological range and promoting a more lasting expressibility (Ahmed et al, 2019; Zhao et al, 2022). More extensive, prospective studies employing lipidomic analysis at several time points during treatment are warranted and currently underway by our group. Telangiectatic thrombosis: eyelid telangiectasia is a hallmark of MGD, and it is hypothesised that these abnormal vascular structures may work as an inducer, propagator and reservoir for pro‐inflammatory mediators (Bron et al, 2017; Dell et al, 2017; Schaumberg et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have promoted this as a contributary mechanism of IPL (Dell et al, 2017; Gupta et al, 2016), though others voice scepticism due to the short duration and limited effect on temperature (Albietz & Schmid, 2018; Craig et al, 2015). However, recent publications describe alterations of the lipidomic profile of DED patients following IPL treatment, thus theoretically lowering the phase‐transition temperature back towards the physiological range and promoting a more lasting expressibility (Ahmed et al, 2019; Zhao et al, 2022). More extensive, prospective studies employing lipidomic analysis at several time points during treatment are warranted and currently underway by our group. Telangiectatic thrombosis: eyelid telangiectasia is a hallmark of MGD, and it is hypothesised that these abnormal vascular structures may work as an inducer, propagator and reservoir for pro‐inflammatory mediators (Bron et al, 2017; Dell et al, 2017; Schaumberg et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A later study employed liquid chromatography tandem mass spectrometry to analyse and compare the lipidomic profiles of 10 healthy controls and 26 MGD patients before and after IPL treatment (Zhao et al, 2022). In total, 323 lipid species were identified, 41 of which differed between subjects and controls at baseline, and 24 lipid species altered following treatment.…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…The potential mechanism of action of IPL in MGD management is poorly understood but may involve warming (although observed eyelid temperature change is minimal [ 113 ]), thrombosis of abnormal blood vessels, inhibition of bacterial growth, and/or photomodulation effects on the meibomian glands [ 114 ]. It is possible that IPL may alter tear film lipids [ 115 , 116 ] and tear cytokines [ 114 , 117 ]. The efficacy of IPL for the treatment of MGD was evaluated in a meta-analysis that included nine studies (539 patients in total) and found that IPL combined with meibomian gland expression was superior to meibomian gland expression alone based on TFBUT and OSDI scores, but not SPEED scores [ 118 ].…”
Section: Management Of Dry Eye Disease Associated With Meibomian Glan...mentioning
confidence: 99%
“…Finally, atrophy and dropout of MGs in some cases could appear [6][7] . MGD is a prevalent dry eye disorder (DED) with an estimated prevalence range between 3.5% and 70% [1,[8][9][10] , it constitutes the primary underlying pathology within the EDE subtype [11][12] . In addition, it is known that MGD is a chronic and progressive condition [2,13] , so it is crucial to identify clinical approaches that can successfully address this underlying condition.…”
Section: Introductionmentioning
confidence: 99%